BMC Musculoskeletal Disorders - Jensen, Barbara; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Musculoskeletal Disorders is an open access, peer-reviewed journal that considers articles on all aspects of the prevention, diagnosis and management of musculoskeletal disorders, as well as related molecular genetics, pathophysiology, and epidemiology. Studies investigating the systemic nature of rheumatic diseases, not related to specific musculoskeletal manifestations, are directed to submit to BMC Rheumatology. Our journal welcomes submissions in the following broad areas of research related to musculoskeletal disorders: Clinical research and trial interventions on topics, such as osteoarthritis, joint pain, orthopedics and osteoporosis. Computational modelling including gait analysis, biomechanics and kinematics. Rehabilitation devices like prosthetics and orthotics, as well as exercise- and physical-based therapies. Digital technologies such as artificial intelligence, data science, medical sensors, mobile apps and telehealth. Epidemiology including cohorts, genetic association and prevalence studies. Healthcare research applying methods in economic evaluation and prognostic outcomes in musculoskeletal care. Occupational, physical activity and work safety and studies on their correlates to musculoskeletal health and disease. Pathophysiology when studies validate findings on biomarkers, cell signalling pathways, and infection related to the musculoskeletal system. Qualitative research methods incorporating psychometric, semi-structured interviews or thematic analysis, especially those incorporating Patient and Public Involvement (PPI). Radiology and diagnostic imaging techniques like computed tomography, magnetic resonance imaging and ultrasound. Surgical advancements in procedures such as arthroplasty, arthroscopy and robotics. As a BMC Series journal, BMC Musculoskeletal Disorders does not make editorial decisions based on the perceived interest or potential impact of a study. Manuscripts are considered for publication if they are scientifically valid. For research articles, this includes having a clearly defined and sound research question, appropriate methodology and analysis, and adherence to community-agreed standards relevant to the field.
Keywords: Orthopedics; Clinical psychology; Rehabilitation; Mentally ill$1 (BRehabilitation.s; Rheumatology; Sports medicine; Internal medicine; Epidemiology; Orthopaedics; Rehabilitation Psychology; Rheumatology; Sports Medicine; Internal Medicine; Epidemiology